Herita, een hart voor erfgoed - Van Hecke, Tanya (Antwerpen : Herita vzw, 2013)
Abdijsite Herkenrode - Kapel O -L -Vr - Steenbergen, Oud-Heverlee - Kapel O -L -Vr - Kinkenberg, Voeren - Kasteel Beauvoorde, Veurne - Kasteel van Horst - Molen van Hoeke, Damme - Paleis op de Meir, Antwerpen - Paviljoen De Notelaer, Bornem - St-Annakapel, Voeren - St-Donatiustoren, Leuven - Tramsite Schepdaal - Den Wolsack en de Hofkamer, Antwerpen